Preparation method and application of zinc ion battery anode material based on nanocellulose fibrils and cellulose nanocrystals
By introducing nanocellulose filaments and cellulose nanocrystals into the zinc ion battery anode material, a three-dimensional conductive network is formed, which solves the dendrite growth and water-induced corrosion problems of zinc metal anode, and significantly improves the Coulomb efficiency and cycle life of the battery. .
Patent Information
- Application Number
- CN202411607503.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The zinc metal anode in zinc ion batteries faces the problems of dendrites growth and water-induced corrosion, resulting in poor reversibility and cyclic stability.
By mixing nanocellulose filaments and cellulose nanocrystals with zinc powder and carbon nanotubes, the preparation plan is optimized to form a three-dimensional porous conductive network to enhance the contact area between the electrode material and the electrolyte.
It significantly improves the Coulomb efficiency and cycle life of the battery, reduces the formation of dendrites, and improves the cycle stability and reversibility of the electrodes.
Smart Images

Figure CN119480985A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer nanocomposite materials, and in particular to a preparation method and application of a zinc ion battery anode material based on nanocellulose fibrils and cellulose nanocrystals. Background Art
[0002] In recent years, zinc-ion batteries have been widely used due to their high theoretical specific capacity (820 mAh g -1 ) and low redox potential (−0.762 V vs. SHE, standard hydrogel electrode), it has attracted extensive attention in the field of energy storage and conversion. However, zinc metal anodes face the persistent challenges of dendrite growth and water-induced corrosion, which seriously impair the reversibility and cycling stability of zinc anodes in zinc-ion batteries (AZIBs). The formation of zinc dendrites usually originates from the inhomogeneous deposition of zinc on the metal anode, which may be caused by the inhomogeneous electric field distribution and the heterogeneous solid electrolyte interface (SEI) generated by the decomposition of organic electrolytes. Due to the hexagonal close-packed (hcp) structural characteristics of zinc, the (0002) crystal plane is preferentially exposed, resulting in the formation of convex surfaces on the metal anode. The presence of this convex surface makes zinc ions more inclined to accumulate at the top of the convexity when deposited, forming the so-called "tip effect". If the growth of dendrites is too intense, the thick and sharp dendrites formed may penetrate the separator of the battery, causing battery short circuit and failure. Even in the early stage of dendrite growth, it may promote the formation of zinc sulfate hydroxide (ZSH) and hydrogen evolution reaction on the anode side. The generation of inert byproduct ZSH will form a passivation layer on the electrode surface, exacerbating the dendrite problem, while the generation of hydrogen is usually harmful to battery performance. In order to solve the interfacial stability problem of zinc metal anode in aqueous zinc-ion batteries in practical applications, dendrites can be reduced by preparing a surface modification layer, such as carbon nanotubes (CNTs), GO, reduced graphene oxide (rGO), graphite, etc., which can be allocated to a part of the negative electrode charge, thereby having a higher electrochemical activity.
[0003] The mechanical properties of pure carbon nanotubes and Zn powders are poor and cannot form a film. Usually, it is necessary to add a binder (such as carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), etc.), optimize the ratio of CNT and Zn powder, and perform surface modification (such as oxidation, reduction or grafting functionalization) to solve this problem. Therefore, how to improve the mechanical strength and electrochemical performance of zinc metal negative electrodes by improving them is the key to preparing high-performance zinc-ion batteries. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a zinc ion battery anode material based on nanocellulose fibrils and cellulose nanocrystals and its application to solve the above-mentioned problems in the background technology. The present invention uses nanocellulose fibrils and cellulose nanocrystals as raw materials and optimizes the corresponding preparation scheme to give the product a unique nanostructure and form a three-dimensional porous conductive network, thereby significantly increasing the contact area between the electrode material and the electrolyte and promoting the Zn 2+ The rapid diffusion and uniform deposition of the nanostructured carbon have a positive impact on improving the Coulombic efficiency and extending the cycle life of the battery.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is to provide a method for preparing a zinc ion battery anode material, comprising the following steps:
[0007] Mix zinc powder, carbon nanotubes (CNTs), cellulose nanofibrils (CNFs), cellulose nanocrystals (CNCs) and water (DI) to obtain a precursor solution;
[0008] The precursor solution is filtered to obtain a filter membrane, freeze-dried, and pressure-treated to obtain the zinc ion battery anode material.
[0009] Preferably, the method of mixing zinc powder, carbon nanotubes, nanocellulose fibrils, cellulose nanocrystals and water is: nanocellulose fibrils and cellulose nanocrystals are mixed to obtain a suspension, which is then dropped into a carbon nanotube aqueous solution under stirring conditions, and then zinc powder is added for stirring and ultrasonic crushing.
[0010] Preferably, the crushing power ratio of the ultrasonic crushing is 70%, the crushing mode is on for 2s and off for 1s, and the total crushing time is 60 min.
[0011] The ultrasonication of the present invention can improve dispersibility and uniformity.
[0012] Preferably, the size range of the zinc powder is 15-53 μm; the length range of the carbon nanotube is 0.5-2 μm, and the diameter range is 10-20 nm; the length range of the nanocellulose fibrils is 5-10 μm; and the diameter range of the cellulose nanocrystals is 100-200 nm.
[0013] Preferably, the ratio of the total mass of the zinc powder, carbon nanotubes, nanocellulose fibrils and cellulose nanocrystals to water is 450-500 mg:45-55 mL; the mass ratio of the total mass of the nanocellulose fibrils and cellulose nanocrystals to the zinc powder and carbon nanotubes is 1:8:1; the mass ratio of the nanocellulose fibrils and cellulose nanocrystals is 4-9:1.
[0014] Preferably, the mass ratio of the nanocellulose fibrils to the cellulose nanocrystals is 8:1.
[0015] Preferably, the filtering method is vacuum filtration.
[0016] Preferably, the freeze-drying cold trap temperature is -60°C and the time is 24 hours.
[0017] Preferably, the pressure of the pressurization treatment is 10 MPa.
[0018] The main functions of the pressure treatment of the present invention are to improve the filtration efficiency, shorten the filtration time, and promote the separation and purification of the filtrate.
[0019] The second technical solution of the present invention is to provide a zinc ion battery anode material obtained according to the above preparation method.
[0020] Preferably, the conductivity of the zinc ion battery anode material is 847-1250 S / m, and the specific surface area is 29-38m 2 / g.
[0021] The third technical solution of the present invention is to provide an application of the above-mentioned zinc ion battery anode material in the preparation of zinc ion batteries.
[0022] Preferably, the zinc ion battery is a symmetrical battery, a coin battery or a flexible battery.
[0023] The technical principles of the present invention are as follows:
[0024] The present invention prepares a Zn / carbon nanotube / nanocellulose fibril / cellulose nanocrystal composite aerogel film by adjusting the mixing method and ratio of zinc powder, carbon nanotubes, nanocellulose fibrils and cellulose nanocrystals, and performing directional freezing and vacuum freeze-drying after vacuum filtration. A three-dimensional conductive network is constructed through CNF, CNC and CNT in the aerogel.
[0025] Compared with the traditional solution using zinc powder and carbon nanotubes as raw materials, the present invention can increase more hydrogen bonding sites by introducing nanocellulose fibrils and cellulose nanocrystals, and endow it with a unique nanoscale structure, which can construct multiple reversible conductive networks and enhance the mechanical properties of the aerogel. This nanostructure can homogenize the interfacial electric field, provide an electron transfer path, improve the electronic conductivity of the membrane, and help improve the charge transfer efficiency.
[0026] The present invention has found through experiments that if CNF and CNC are omitted, the mechanical properties of the mixed hydrogel deteriorate and it is difficult to form a film, resulting in poor sensing performance of the hydrogel. If only CNF is omitted, the filter membrane system obtained after filtration is almost powdery, which is difficult to peel off and form a film normally, and thus cannot be prepared into a final product.
[0027] In addition, the ratio of CNF to CNC in the present invention also needs to be specifically limited. When the mass ratio of nanocellulose fibrils to cellulose nanocrystals is higher or lower than 8:1, the number of dendrites produced in the product after cycling increases relatively, and the cycling performance is poor.
[0028] When the zinc ion battery anode material of the present invention is prepared into a symmetrical battery, the cycle efficiency of 6000 cycles is close to 100%, and the cycle performance is excellent.
[0029] The beneficial technical effects of the present invention are as follows:
[0030] The present invention uses nanocellulose fibrils and cellulose nanocrystals as raw materials and optimizes the corresponding preparation scheme to give the product a unique nanostructure and form a three-dimensional porous conductive network, thereby significantly increasing the contact area between the electrode material and the electrolyte and promoting the Zn 2+ The rapid diffusion and uniform deposition of Zn have a positive effect on improving the Coulombic efficiency and extending the cycle life of the battery. In addition, this nanostructure provides sufficient space for the volume change of Zn, effectively reducing the formation of dendrites, thereby improving the cycle stability and reversibility of the electrode, so that the product of the present invention has excellent conductivity and high cycle efficiency. At the same time, by adding the three-dimensional conductive network structure constructed by CNF and CNC, the hydrogen evolution side reaction and the generation of inert by-products are effectively suppressed, and the consumption of electrolyte is reduced, which has a positive effect on improving the Coulombic efficiency and extending the cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a macroscopic picture of the filter membrane in Comparative Example 1.
[0033] Figure 2 The figure is a physical picture of the bending test of the zinc ion battery anode material in Example 2. Among them, a is the physical picture before bending, b and c are the physical pictures at different angles during the bending process, and d is the physical picture after bending.
[0034] Figure 3 The charge and discharge cycle test data of the symmetrical battery prepared with the products of Examples 1-4.
[0035] Figure 4The SEM images of the anode material of the symmetrical battery prepared with the products of Example 2 and Example 3 after 6000 cycles. Among them, a is Example 2, and b is Example 3.
[0036] Figure 5 Schematic diagram of the cycle efficiency of a symmetrical battery prepared using the products of Examples 1-4.
[0037] Figure 6 This is the SEM image of the zinc ion battery anode material in Example 1. DETAILED DESCRIPTION
[0038] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0039] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0041] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.
[0042] The size range of the zinc powder used in the following embodiments and comparative examples of the present invention is 34 μm; the length range of the carbon nanotubes is 1.3 μm, and the diameter range is 15 nm; the length range of the nanocellulose fibrils is 7.5 μm; and the diameter range of the cellulose nanocrystals is 150 nm.
[0043] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.
[0044] Example 1
[0045] A method for preparing a zinc ion battery anode material:
[0046] Prepare 500 mg of zinc powder, carbon nanotubes (CNT), nanocellulose fibrils (CNF) and cellulose nanocrystals (CNC) (wherein the mass ratio of the total mass of CNF and CNC to zinc powder and CNT is 1:8:1, and the mass ratio of CNF and CNC is 4:1), first disperse the nanocellulose fibrils and cellulose nanocrystals in 25 mL of deionized water and mix well to obtain a suspension, then disperse the carbon nanotubes in 25 mL of deionized water and mix well to obtain a carbon nanotube aqueous solution, then drop the carbon nanotube aqueous solution into the suspension under stirring conditions, then add zinc powder, stir and ultrasonically crush (the ultrasonic crushing power ratio is 70%, the crushing mode is on for 2 seconds, off for 1 second, and the total crushing time is 60 minutes) to obtain a precursor solution;
[0047] The precursor solution was vacuum filtered, and then the obtained filter membrane was peeled off from the filter membrane, and then placed in an ultra-low temperature refrigerator and frozen at -45°C for 24 hours, and then freeze-dried (cold trap temperature -60°C, time 24 hours, vacuum degree 10Pa), and then pressurized at 10 MPa to obtain a zinc ion battery anode material.
[0048] Figure 6 This is the SEM image of the zinc ion battery anode material in Example 1.
[0049] Depend on Figure 6 It can be seen that the cross-section of the zinc ion battery anode material prepared in this embodiment is a layered structure, and the zinc balls are embedded in the plane interwoven by the carbon nanotubes, nanocellulose fibrils and cellulose nanocrystals.
[0050] Example 2
[0051] A method for preparing a zinc ion battery anode material:
[0052] Prepare 500 mg of zinc powder, carbon nanotubes (CNT), nanocellulose fibrils (CNF) and cellulose nanocrystals (CNC) (wherein the mass ratio of the total mass of CNF and CNC to zinc powder and CNT is 1:8:1, and the mass ratio of CNF and CNC is 6:1), first disperse the nanocellulose fibrils and cellulose nanocrystals in 25 mL of deionized water and mix well to obtain a suspension, then disperse the carbon nanotubes in 25 mL of deionized water and mix well to obtain a carbon nanotube aqueous solution, then drop the carbon nanotube aqueous solution into the suspension under stirring conditions, then add zinc powder to stir and ultrasonically crush (the ultrasonic crushing has a crushing power ratio of 70%, a crushing mode of on 2s, off 1s, and a total crushing time of 60 min);
[0053] The precursor solution was vacuum filtered, and then the obtained filter membrane was peeled off from the filter membrane, freeze-dried (cold trap temperature -60°C, time 24h, vacuum degree 10Pa), and then pressure treated at 10 MPa to obtain the zinc ion battery anode material.
[0054] Example 3
[0055] A method for preparing a zinc ion battery anode material:
[0056] Prepare 500 mg of zinc powder, carbon nanotubes (CNT), nanocellulose fibrils (CNF) and cellulose nanocrystals (CNC) (wherein the mass ratio of the total mass of CNF and CNC to zinc powder and CNT is 1:8:1, and the mass ratio of CNF and CNC is 8:1), first disperse the nanocellulose fibrils and cellulose nanocrystals in 25 mL of deionized water and mix well to obtain a suspension, then disperse the carbon nanotubes in 25 mL of deionized water and mix well to obtain a carbon nanotube aqueous solution, then drop the carbon nanotube aqueous solution into the suspension under stirring conditions, then add zinc powder to stir and ultrasonically crush (the ultrasonic crushing has a crushing power ratio of 70%, a crushing mode of on 2s, off 1s, and a total crushing time of 60 min);
[0057] The precursor solution was vacuum filtered, and then the obtained filter membrane was peeled off from the filter membrane, freeze-dried (cold trap temperature -60°C, time 24h, vacuum degree 10Pa), and then pressure treated at 10 MPa to obtain the zinc ion battery anode material.
[0058] The zinc ion battery anode material prepared in Example 3 was analyzed by cyclic voltammetry (CV) curve to study the kinetic behavior of the zinc ion battery anode material. It was found that the CV graph was consistent with the GCD profile. In addition, as the scan rate increased, the peak current increased accordingly, and the CV curve maintained its integrity.
[0059] Example 4
[0060] A method for preparing a zinc ion battery anode material:
[0061] Prepare 500 mg of zinc powder, carbon nanotubes (CNT), nanocellulose fibrils (CNF) and cellulose nanocrystals (CNC) (wherein the mass ratio of the total mass of CNF and CNC to zinc powder and CNT is 1:8:1, and the mass ratio of CNF and CNC is 9:1), first disperse the nanocellulose fibrils and cellulose nanocrystals in 25 mL of deionized water and mix well to obtain a suspension, then disperse the carbon nanotubes in 25 mL of deionized water and mix well to obtain a carbon nanotube aqueous solution, then drop the carbon nanotube aqueous solution into the suspension under stirring conditions, then add zinc powder, stir and ultrasonically crush (the crushing power ratio of the ultrasonic crushing is 70%, the crushing mode is on for 2 seconds, off for 1 second, and the total crushing time is 60 minutes);
[0062] The precursor solution was vacuum filtered, and then the obtained filter membrane was peeled off from the filter membrane, freeze-dried (cold trap temperature -60°C, time 24h, vacuum degree 10Pa), and then pressure treated at 10 MPa to obtain the zinc ion battery anode material.
[0063] By observing the cross-sections of the zinc powder / carbon nanotube / nanocellulose fibril (CNF) / cellulose nanocrystal (CNC) composite zinc ion battery anode material prepared in Example 4 before and after cycling, it is clearly found that the zinc ion battery anode becomes significantly thicker after cycling.
[0064] Comparative Example 1 (omitting the addition of nanocellulose fibrils and nanocellulose crystals and supplementing with an equal mass of carbon nanotubes)
[0065] Disperse 500 mg of zinc powder and carbon nanotubes (CNT) in 50 mL of deionized water (wherein the mass ratio of zinc powder to CNT is 8:1) and mix well to obtain a precursor solution;
[0066] The precursor solution was vacuum filtered to obtain a filter membrane. Since the obtained filter membrane system was almost in powder form and difficult to be normally peeled off from the filter membrane, subsequent freeze-drying and other operations were not performed.
[0067] Figure 1 This is a physical picture of the filter membrane in Comparative Example 1.
[0068] Depend on Figure 1 It can be seen that without adding CNF and CNC, the filter membrane system obtained after filtration is almost powdery, which is difficult to peel off and form a membrane normally, and it is impossible to prepare the final product.
[0069] Effect verification
[0070] 1. The zinc ion battery anode material obtained in Example 2 was subjected to a 90° repeated bending test, which was repeated 5 times in total.
[0071] Figure 2The figure is a physical picture of the bending test of the zinc ion battery anode material in Example 2. Among them, a is the physical picture before bending, b and c are the physical pictures at different angles during the bending process, and d is the physical picture after bending.
[0072] Depend on Figure 2 It can be seen that after the folding test, the product did not produce significant geometric deformation.
[0073] After coin battery assembly, it showed a high cycle retention rate of no less than 98% after 1500 cycles.
[0074] 2. The zinc ion battery anode materials of each embodiment and comparative example were assembled into batteries, and their corresponding electrochemical properties were tested.
[0075] Assembly of symmetrical battery:
[0076] Two zinc ion battery anode materials (ZTFC) were used as electrodes, and 0.2M ZnSO4 and 0.2M MnSO4 were used as electrolytes to assemble a CR2032 coin symmetrical battery. A glass cellulose membrane with a diameter of about 19mm was used as a separator. Before the electrochemical test, the assembled battery was placed in the air for 10 hours to stabilize its performance and facilitate testing.
[0077] Assembly of coin-type aqueous zinc-ion batteries (Azibs):
[0078] To prepare the cathode, a slurry consisting of γ-MnO2 (70 wt%), carbon black (20 wt%) and polyvinylidene fluoride (10 wt%) dispersed in N-methylpyrrolidone solvent was coated on nickel foam, then dried at 60 °C for 24 h and then pressurized at 10 MPa; the coin cell was assembled with ZTFC as the anode, a glass cellulose membrane with a diameter of about 19 mm as the separator, and a mixed aqueous solution containing 0.2MZnSO4 and 0.2M MnSO4 as the electrolyte. 200mL of electrolyte was added to each coin-type aqueous zinc-ion battery.
[0079] Figure 3 The charge and discharge cycle test data of the symmetrical battery prepared with the products of Examples 1-4.
[0080] Figure 3 In the embodiment, CNF:CNC=4:1 represents Example 1, CNF:CNC=6:1 represents Example 2, CNF:CNC=8:1 represents Example 3, and CNF:CNC=9:1 represents Example 4.
[0081] Figure 4 The SEM images of the anode material of the symmetrical battery prepared with the products of Example 2 and Example 3 after 6000 cycles. Among them, a is Example 2, and b is Example 3.
[0082] Figure 5 Schematic diagram of the cycle efficiency of a symmetrical battery prepared using the products of Examples 1-4.
[0083] Figure 5 Among them, 4:1 represents Example 1, 6:1 represents Example 2, 8:1 represents Example 3, and 9:1 represents Example 4.
[0084] Depend on Figure 3 It can be seen that when the current density is stable at 0.5mA / cm 2 When the product of Example 3 was cycled for 6000 times, the voltage was stable, while at other CNF:CNC ratios, the voltage fluctuated significantly. This may be because other products would produce a large number of dendrites during the cycle ( Figure 4 a is Example 2, Figure 4 b is Example 3), which reduces the stability of the battery.
[0085] Depend on Figure 5 It can be seen that the zinc ion battery anode material prepared in Example 3 has the best cycle efficiency and cycle stability when assembled into coin cells compared with the products of other examples, maintaining a cycle efficiency of 98% and a capacity retention rate of 99%.
[0086] In summary, the three-dimensional conductive skeleton structure of the product of the present invention makes the electric field at the interface uniform, which is conducive to the transfer of electrons, thereby enhancing the electronic conductivity of the film and accelerating the transfer of charges. It has been measured that the battery prepared by the product of the present invention has a high coulomb efficiency, good battery cycle performance and reversibility, and no obvious polarization phenomenon during the charge and discharge process.
[0087] ZTFC anodes with different proportions deformed to different degrees after cycling. After cycling, the Zn on the surface of the product of Example 3 grew in an orderly manner in the horizontal direction (epitaxial growth) and the vertical direction, and dense, uniform, and dendrite-free Zn deposition and growth can be achieved, and the surface remains relatively smooth; while other surfaces become relatively rough and thicker. The formation of dendrites first decreases and then increases. By optimizing the addition ratio of CNF and CNC, the pore structure and wettability of the product are improved, and the diffusion and deposition ability of zinc are enhanced. This is mainly because, at this ratio, the change of local current density during the galvanizing process is minimized, effectively preventing the early growth of zinc dendrites; while the inappropriate ratio leads to a denser electrode structure, reduces the active reaction area, hinders the electrolyte-electrode interaction, and promotes the formation of zinc dendrites.
[0088] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a zinc ion battery anode material, characterized in that: The following steps are involved: mixing zinc powder, carbon nanotubes, nanocellulose fibrils, cellulose nanocrystals and water to obtain a precursor solution; The precursor solution is filtered to obtain a filter membrane, freeze-dried, and pressure-treated to obtain the zinc ion battery anode material.
2. The preparation method according to claim 1, characterized in that: The size range of the zinc powder is 15-53 μm; the length range of the carbon nanotube is 0.5-2 μm, and the diameter range is 10-20 nm; the length range of the nanocellulose fibril is 5-10 μm; and the diameter range of the cellulose nanocrystal is 100-200 nm.
3. The preparation method according to claim 1, characterized in that: The ratio of the total mass of the zinc powder, carbon nanotubes, nanocellulose fibrils and cellulose nanocrystals to water is 450-500 mg:45-55 mL; the mass ratio of the total mass of the nanocellulose fibrils and cellulose nanocrystals to the zinc powder and carbon nanotubes is 1:8:1; the mass ratio of the nanocellulose fibrils to cellulose nanocrystals is 4-9:
1.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the nanocellulose fibrils to the cellulose nanocrystals is 8:
1.
5. The preparation method according to claim 1, characterized in that: The filtering method is vacuum filtration.
6. The preparation method according to claim 1, characterized in that: The cold trap temperature of the freeze drying is -60°C and the time is 24h.
7. The preparation method according to claim 1, characterized in that: The pressure of the pressurization treatment is 10 MPa.
8. A zinc ion battery anode material obtained according to the preparation method according to any one of claims 1 to 7.
9. The zinc ion battery anode material according to claim 8, characterized in that The conductivity of the zinc ion battery anode material is 847-1250S / m, and the specific surface area is 29-38m 2 / g.
10. Use of the zinc ion battery anode material according to claim 8 or 9 in preparing a zinc ion battery.
Citation Information
Patent Citations
Cellulose-based integrated zinc ion battery and preparation method thereof
CN111785898A
High-performance zinc-based aqueous electrolyte and application thereof
CN116826194A
Dispersion, composite, and producing methods therefor
US20240183107A1